STRUKTUR KOMUNITAS MANGROVE DI DESA LESAH, KECAMATAN TAGULANDANG, KABUPATEN SITARO - Indra Asman; Calvyn F A Sondak; Joshian N W Schaduw; Deislie R H Kumampung; Medy Ompi; Haryani Sambali (JURNAL PESISIR DAN LAUT TROPIS, 2020)
Mangroves are forests that grow in brackish water and are affected by tides and seawater, and these forests grow specifically in places where there are pavement and accumulation of organic material. The purpose of this research is to identify the types of mangroves and determine the structure of the mangrove community in Lesah Village. This research was conducted from September to October 2019. The method used in this research is the quadrant line transect method. The types of mangroves were identified with identification books. Community structure data taken are density, frequency, dominance and important value index (IVI) and then analyzed with Microsoft Excel program. Based on the results of the research, there are 2 types of mangroves found in the research location, Rhizophora stylosa and Sonneratia alba. The highest density value (0.122 ind / m2), relative density (81.88%), frequency types (1), relative frequency (50%). Closure types (1.83 m2), types of relative closure (50.18%), the highest important value index at the research site was (182.12%). The results of the mangrove ecological index data analysis for the diversity index value (0.51), dominance (0.73). Keywords: Structure Community, Mangrove, Lesah Village. Abstrak Mangrove adalah hutan yang tumbuh di air payau, dan dipengaruhi oleh pasang surut air laut dan hutan ini tumbuh khususnya di tempat-tempat di mana terjadi pelumpuaran dan akumulasi bahan oraganik. Tujuan dari penelitian adalah mengidentifikasi jenis-jenis mangrove dan mengetahui struktur komunitas mangrove di Desa Lesah. Penelitian dilaksanakan dari September-Oktober 2019. Metode yang digunakan adalah metode line transek kuadran. Jenis-jenis mangrove di identifikasi dengan bantuan buku identifikasi. Data struktur komunitas yang di ambil adalah kerepatan, ferkuensi, dominasi dan indeks nilai penting(INP) dan kemudian di analisa dengan bantuan program computer Microsoft Excel. Berdasarkan hasil penelitian terdapat 2 jenis mangrove yang terdiri dari, Rhizophora stylosa dan Sonneratia alba. Nilai kerepatan tertinggi (0.122 ind/m2), kerapatan relatif jenis (81.88%), frekuensi jenis (1), frekuensi relatif jenis (50%). Penutupan jenis (1.83 m2), penutupan relatif jenis (50.18%), indeks nilai penting tertinggi dilokasi penelitian adalah (182.12%). Hasil analisis data indeks ekologi mangrove untuk nilai indeks keanekaragaman (0.51), dominasi(0.73). Kata Kunci: Struktur Komunitas, Mangrove, Desa Lesah.